Healthy Education in The Middle of Pandemi Covid-19 Through The Use of Social Media - Fitri Fatonah; Sugiyanto Sugiyanto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Strategic and rapid efforts are needed to overcome the spread of Covid-19, one of them is by counseling through social media in order that scientific information is provided. The existence of so called Social Abdication Program of UNS in the form of  Field Work Lecture addresses this issue, takes a theme "Education on the Exercise of Clean and Healthy Behavior (PHBS) and the Use of Medicines Provision in the Context of Preventing Covid-19 in RT 01 RW 01 Klegenwonosari Village, Klirong, Kebumen". The program uses social media (online) due to its need to maintaining physical distancing. However it also uses direct face-to-face activities on program socialization. The results of this community service activity show that: 1) there is an public awareness about facts about Covid-19, 2) the application of PHBS and health tips, and understanding DAGUSIBU. Through quiz myths and fact, wider community can test their understanding of Covid-19 issues.